2015
DOI: 10.1093/mnras/stv1198
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mock tidal streams

Abstract: In this paper we discuss a method for the generation of mock tidal streams. Using an ensemble of simulations in an isochrone potential where the actions and frequencies are known, we derive an empirical recipe for the evolving satellite mass and the corresponding mass loss rate, and the ejection conditions of the stream material. The resulting stream can then be quickly generated either with direct orbital integration, or by using the action-angle formalism. The model naturally produces streaky features within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 48 publications
4
122
0
Order By: Relevance
“…When S15 concluded that the progenitor of the Ophiuchus stream could not have been on its current orbit (measured by S15) for more than ∼400 Myr, they assumed the stream is on a regular, non-resonant orbit. However, as we already mentioned in Section 1, fanning can be a signature of a stream on a chaotic orbit (Fardal et al 2015;Price-Whelan et al 2016). If the fanning of the Ophiuchus stream is due to the stream being on a chaotic orbit, then the orbital parameters measured by S15 today were likely different in the past 12 Gyr.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…When S15 concluded that the progenitor of the Ophiuchus stream could not have been on its current orbit (measured by S15) for more than ∼400 Myr, they assumed the stream is on a regular, non-resonant orbit. However, as we already mentioned in Section 1, fanning can be a signature of a stream on a chaotic orbit (Fardal et al 2015;Price-Whelan et al 2016). If the fanning of the Ophiuchus stream is due to the stream being on a chaotic orbit, then the orbital parameters measured by S15 today were likely different in the past 12 Gyr.…”
Section: Discussionmentioning
confidence: 87%
“…This fanning may arise if the progenitor is on a chaotic orbit, common in triaxial or otherwise complex gravitational potentials (bottom panels of Figure 11 of Fardal et al 2015; Figure 7 of Price-Whelan et al 2015); or it may arise through interactions with dark matter subhalos (bottom left panel of Figure 3 of Bonaca et al 2014). Hence, stream-fanning-if observable-could become a new tool for studying these dynamical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…However, the observational constraints on Herc are not sufficient for such a complex approach. The same holds true for a more complex model of Herc with additional model parameters for, e.g., rotation of the progenitor (Amor- (Fardal, Huang & Weinberg 2015). Given the low number of observational constraints, we would likely be over-fitting our data without getting meaningful constraints on the model parameters.…”
Section: Streakline Model Setupmentioning
confidence: 86%
“…This means that mass loss due to subhalo shocking on the progenitor is rare, and that the orbits of the particles that are bound to the progenitor should be irrelevant. Therefore, rather than treating the progenitor and stream as an N-body system, "shortcut" methods (e.g., Küpper et al 2012;Bonaca et al 2014;Gibbons et al 2014;Fardal et al 2015) which eject test particles at the progenitor's Lagrange points are promising alternatives. These methods potentially allow realistic streams to be generated quickly, so they are worth adopting in the future.…”
Section: Stream Progenitor and Orbitsmentioning
confidence: 99%